IMPLIKASI PENDIDIKAN KARAKTER DALAM KISAH UWAIS AL – QORNI : SEJARAH PENDIDIKAN ISLAM BAGI GENERASI MILLENNIAL - Pramudita, Nafil Siraj; Nurjanah; Rahma, Novi Putri; Pratama, Mohamad Raka; Abdullah, Dimas Bayu Ajhi Prakoso (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research talks about the implications of character education in the story of Uwais Al Qarni on the history of Islamic education and its relevance for the millennial generation. Uwais Al Qarni is also a figure who is known to have noble characteristics, such as respect for parents, strong patience, and asceticism towards the world. Through analysis of his life story, this research focuses on character values that can be developed in the Islamic education system. This studi can also explore how these values can be adopted and applied in the context of modern education to form a millennial generation with noble morals. The research results show that developing Uwais Al Qarni character values can expand the educational curriculum and strengthen the morals of the millennial generation in facing today’s social and technological problems. These findings emphasize the improtance of character education based on Islamic historical examples to form a generation with noble character and ready to face the challenges of the end times.